Modelling and testing consumer trust dimensions in e-commerce - Oliveira, Tiago (2019)
Oliveira, T., Alhinho, M., Rita, P., & Dhillon, G. (2017). Modelling and testing consumer trust dimensions in e-commerce. Computers in Human Behavior, 71, 153-164. https://doi.org/10.1016/j.chb.2017.01.050